Development And Characterization Of Eugenol In Cinnamon Leaf Oil Nanocream For Wound Healing - Zainol, Nor Azah (2014)
Cinnamon (Cinnamomum zeylanicum) leaf oil contains high percentage of eugenol and has antimicrobial, antioxidant and anti-inflammatory activities. However, the undiluted oil can cause irritation to the skin. Therefore, to avoid irritation cinnamon leaf oils was formulated into nanocream. The nanocream base was prepared using palm oil, buffer pH 5.5 and surfactants (Tween, Span and Carbitol) at different HLB values of 13.71, 11.13, 9.84 for Tween 80 and Span 65 while 13.92, 12.84 and 10.68 for Tween 80 and Carbitol. Fifteen nanocream base formulations were selected from nanocream areas in three pseudo-ternary phase diagrams, and tested for accelerated stability study. Only four formulations passed the test, and these formulations were modified by adding 2 % cetostearyl alcohol as thickening agent, to improve their stability. The modified formulations were also subjected to accelerated stability test and three formulations passed the test. The nanocream base formulations were characterized in term of droplet size, zeta potential, apparent viscosity, and rheological properties. It was found that the nanocream base B2(2) was the best formulation and 2% cinnamon leaf oil was incorporated to this formulation. The optimized cinnamon leaf oil formulation consists of buffer pH 5.5, oil (96% palm oil, 2% cinnamon leaf oil and 2% cetostearyl alcohol) and surfactants (70% Tween 80 and 30% Span 65 with HLB value 11.13) at the ratio of 47.4:15.8:36.8.